MENGKAJI PERUBAHAN SOSIAL EKONOMI MASYARAKAT PESISIR CILAMAYA WETAN AKIBAT PEMBANGUNAN PROYEK STRATEGIS NASIONAL PLTGU JAWA-1 POWER - Muhamad Daffa Nugraha; Indra Aditya; Dewi Noor Azijah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to examine the socio-economic impact of the National Strategic Project PLTGU Jawa-1 Power on the living space of the coastal community of Cilamaya Wetan in Karawang Regency, specifically whether PLTGU brings positive or negative impacts on socio-economic conditions. The method used in this study is a case study method. Data collection techniques include field observation, in-depth interviews, and documentation. The data analysis technique used is time-series analysis. The research results show that the development of the Jawa-1 Power Gas-Fired Power Plant creates dualistic economic impacts. On one hand, this project increases economic activity during the construction phase by absorbing local labor and growing the informal sector. On the other hand, vulnerable groups such as tenant farmers and traditional fishermen experience a decline in income due to land conversion and degradation of coastal ecosystems. Environmental impacts include changes in water quality due to waste and a decrease in groundwater quality due to seawater intrusion. The construction process is also assessed to involve less community participation, leading to social conflicts. The coastal community of Cilamaya Wetan, which was previously marginalized economically and geographically, is now also marginalized socially due to the development.